Four Decades of Terms-of-Trade Booms : Saving-Investment Patterns and a New Metric of Income Windfall - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2013)
We study the history of terms-of-trade booms (during 1970-2012), with a focus on Latin America, through the prisms of a simple metric that quantifies the associated income windfall. We also document saving patterns during these episodes and propose a measure of how much of the income windfall was saved. We find that Latin America's terms-of-trade shocks of the last decade have not differed much in magnitude from those observed during the 1970s, but that the associated windfall have been substantially larger. While aggregate saving increased more than in past episodes, the share of the windfall saved (the marginal saving rate) seems to be lower, suggesting that greater aggregate saving reflects mainly the sheer size of the windfall rather than a greater 'effort' to save it. Finally, we find evidence that, while savings during the boom help to increase post-boom income, the composition of such savings matters. Specifically, in past episodes, savings allocated to foreign asset accumulation appear to have contributed more to post-boom income than those devoted to domestic investment.